1999
DOI: 10.1021/bi991070p
|View full text |Cite
|
Sign up to set email alerts
|

Basis of Substrate Binding by the Chaperonin GroEL

Abstract: The molecular chaperonins are essential proteins involved in protein folding, complex assembly, and polypeptide translocation. While there is abundant structural information about the machinery and the mechanistic details of its action are well studied, it is yet unresolved how chaperonins recognize a large number of structurally unrelated polypeptides in their unfolded or partially folded forms. To determine the nature of chaperonin-substrate recognition, we have characterized by NMR methods the interactions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
44
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 72 publications
1
44
0
Order By: Relevance
“…6 and 7). For substrates that are more tightly bound, however, presumably via a greater amount of exposed hydrophobic surface (8), a subsequent step of ATP/GroES binding to the substrate-bound ring ejects the substrate off the cavity wall into a now GroES-encapsulated and hydrophilic so-called cis cavity, where folding commences (9)(10)(11)(12). The reaction proceeds for Ϸ10 seconds before ATP hydrolysis in the cis ring followed by trans ring ATP binding ejects the cis ligands, including substrate polypeptide whether folded or not (11,13,14).…”
mentioning
confidence: 99%
“…6 and 7). For substrates that are more tightly bound, however, presumably via a greater amount of exposed hydrophobic surface (8), a subsequent step of ATP/GroES binding to the substrate-bound ring ejects the substrate off the cavity wall into a now GroES-encapsulated and hydrophilic so-called cis cavity, where folding commences (9)(10)(11)(12). The reaction proceeds for Ϸ10 seconds before ATP hydrolysis in the cis ring followed by trans ring ATP binding ejects the cis ligands, including substrate polypeptide whether folded or not (11,13,14).…”
mentioning
confidence: 99%
“…Results from peptide studies using transferred nuclear Overhauser effects (15)(16)(17) or crystallography (18) have established that various conformations can bind to GroEL; the common feature that mediates binding is exposure of a patch of hydrophobic surface (complementary to the binding surfaces on the apical domains of GroEL). Atomic structures (18,19) implicated two helices on the inner binding surfaces of the apical domains in polypeptide binding, and mutagenesis results (20) also suggest that hydrophobic residues on an underlying extended segment are crucial for substrate binding.…”
Section: The Trapped Folding Intermediatementioning
confidence: 99%
“…Additionally, the GroEL apical domain residues implicated in substrate binding are largely hydrophobic (14). Finally, previous studies on the basis of substrate interaction with GroEL using short model peptides have concluded that the most important determinant of substrate binding is the presentation of a cluster of hydrophobic residues (15)(16)(17).…”
mentioning
confidence: 95%
“…The only evidence addressing the chiral specificity of GroEL/ ES comes from a study that qualitatively demonstrated binding of a short D-peptide to GroEL (16). However, this NMR study required peptide concentrations that greatly exceed physiologic levels and did not localize the interaction to the substratebinding region of GroEL.…”
mentioning
confidence: 99%